Physical-mechanical alterations in Qualea paraensis wood after heat treatment - Medeiros, Dayane Targino de; Batista, Felipe Gomes; Melo, Rafael Rodolfo de; Mascarenhas, Adriano Reis Prazeres; Pedrosa, Talita Dantas (Instituto de Ecología, A.C., 2021)
The objective was to analyze the effect of heat treatments on the physical and mechanical properties of Qualea paraensis wood. Test specimens from 5 lots of wood were submitted to heat treatments using temperatures of 180 °C and 200 °C with periods of 2 h and 4 h. Density (ρa), mass loss (PM), equilibrium moisture content (UE), longitudinal (βl), radial (βr) and tangential (βt) shrinkage, volumetric shrinkage (βv) and anisotropic factor (fa) were determined. Mechanically, the wood was evaluated for strength and stiffness in the tests of static bending (fM and EM) and compression parallel to the fibers (fc0 and Ec0). After the heat treatments, the values of ρ12% increased, on average, by 7.72% and the UE was reduced by 24.3%. The highest values of PM (3.67%) were observed for the exposure time of 2 hours at a temperature of 200 °C. With this treatment, the lowest values of βt (5.73%) and βv (9.69%) were obtained. The thermal treatments increased the bulk density, reduced the equilibrium moisture content, and increased the dimensional stability of the wood. In most heat treatments, a reduction in strength and an increase in stiffness to static bending was observed. There was an increase in strength and stiffness to compression parallel to the grain in all combinations of time and temperature. The greatest dimensional stability with less loss of strength to static bending and parallel compression were obtained with the treatment at 200 °C and time of 2 h.